Mitigating Sports-Related Concussions in Adolescent Athletes: A Systematic Review and Meta-Analysis of Communication and Education Interventions - Giovanna Pedroni; Yara Barrense-Dias; Michael von Rhein; Oliver Gruebner; Chantal Kuske; Barbara Goeggel Simonetti; Marta Fadda; Anne-Linda Camerini (Public Health Reviews)
ObjectivesSports-related concussions (SRCs) in adolescents may pose severe health consequences, which underscores the importance of adequate prevention, early detection, and management. This systematic literature review and meta-analysis aims to synthesize findings from studies evaluating SRC communication and education interventions targeting adolescent athletes and/or their caregivers.MethodsWe included original, peer-reviewed studies published in English between 2014 and 2024. For studies reporting on comparable outcomes, we conducted a meta-analysis based on mean differences between pre- and post-assessment.ResultsOf 2,974 identified records, 22 were included. Most SRC communication and education interventions focused on the North American context, targeted adolescent athletes, and combined digital and in-person communication Interventions were generally more effective in increasing knowledge or awareness than in shifting attitudes or reporting behaviors. The quality of the included studies varied considerably. The studies tended to be short-term and effects appeared independent of the target group, features, or outcome assessments.ConclusionGiven the findings of this review and meta-analysis, future interventions should aim towards long-lasting attitude change fostering intentions to and behaviours promoting the prevention and early detection of SRCs.